STRATEGI PENGELOLAAN PENYIMPANAN KEDELAI (Glycine max L.) TERHADAP SERANGAN KUMBANG KACANG TUNGGAK (Callosobruchus maculatus) - Mutala'liah, Mutala'liah; Arifianto, Robi Aziz; Sardono, Susilo Yudo (Jurnal Agroteknologi, 2025)
Pests and diseases often cause damage to post-harvest commodities. Callosobruchus maculatus is a type of storage insect that damages legume commodities, especially soybeans. This insect cause damage on bean commodities, especially during the storage process. Chemical pesticides are an alternative material which is a quite effective in controlling postharvest pests and diseases. However, pesticide have several side effects on human health and the environment. Therefore, the control action should integrate several compatible methods by applying the principles of integrated of stored product pest management. This review aimed to elaborate various control method to reduce C. maculatus population and increasing soybean productivity. Several techniques regarding on pest control that could be used in controlling C. maculatus comprises of the use of vacuum packaging, storage sanitation, physical control, the use of plant-based pesticides, gamma radiation, and fumigation. By integrating the control techniques, also taking into account in the principal of integrated stored product pest management could be used as a basis of managing stored product pest population in the storage, so that it could suppress the C. maculatus population and reduce the damage on stored commodities both in quality and quantity.